PENGARUH LAYANAN KONSELING INDIVIDU TERHADAP PERILAKU EGOIS SISWA - Sukarman Sukarman (Universitas Pendidikan Mandalika, 2015)
The purpose of this study was to determine the effect of individual counseling services on student selfish behavior at SMA Negeri 1 Pringgasela. The data collection method in this study was a questionnaire method as the main method and the population in this study was 244 people, because the population was more than 100, the sample in this study was 10% x 244 = 24 students. Meanwhile, the data analysis used the t-test formula. Based on the data analysis, the results obtained were the t-count of 3,640 with a t-test value of 2,064 at a significant level of 5% (0.05) with N-1 = 24, thus there was an effect of individual counseling services on selfish behavior in students of SMAN 1 Pringgasela.